Leber's hereditary optic neuropathy-associated ND6 14484T > C mutation caused pleiotropic effects on the complex I, RNA homeostasis, apoptosis and mitophagy - Liang, Min; Ji, Yanchun; Zhang, Liyao; Wang, Xuan; Hu, Cuifang; Zhang, Juanjuan; Zhu, Yiwei; Mo, Jun Q; Guan, Min-Xin (Human molecular genetics, 2022)
Leber's hereditary optic neuropathy (LHON) is a maternally inherited eye disease due to mitochondrial DNA (mtDNA) mutations. LHON-linked ND6 14484T > C (p.M64V) mutation affected structural components of complex I but its pathophysiology is poorly understood. The structural analysis of complex I revealed that the M64 forms a nonpolar interaction Y59 in the ND6, Y59 in the ND6 interacts with E34 of ND4L, and L60 of ND6 interacts with the Y114 of ND1. These suggested that the m.14484T > C mutation may perturb the structure and function of complex I. Mutant cybrids constructed by transferring mitochondria from lymphoblastoid cell lines of one Chinese LHON family into mtDNA-less (ρo) cells revealed decreases in the levels of ND6, ND1 and ND4L. The m.14484T > C mutation may affect mitochondrial mRNA homeostasis, supported by reduced levels of SLIRP and SUPV3L1 involved in mRNA degradation and increasing expression of ND6, ND1 and ND4L genes. These alterations yielded decreased activity of complex I, respiratory deficiency, diminished mitochondrial ATP production and reduced membrane potential, and increased production of reactive oxygen species in the mutant cybrids. Furthermore, the m.14484T > C mutation promoted apoptosis, evidenced by elevating Annexin V-positive cells, release of cytochrome c into cytosol, levels in apoptotic proteins BAX, caspases 3, 7, 9 and decreasing levels in anti-apoptotic protein Bcl-xL in the mutant cybrids. Moreover, the cybrids bearing the m.14484T > C mutation exhibited the reduced levels of autophagy protein LC3, increased levels of substrate P62 and impaired PINK1/Parkin-dependent mitophagy. Our findings highlighted the critical role of m.14484T > C mutation in the pathogenesis of LHON.Leber's hereditary optic neuropathy (LHON) is a maternally inherited eye disease due to mitochondrial DNA (mtDNA) mutations. LHON-linked ND6 14484T > C (p.M64V) mutation affected structural components of complex I but its pathophysiology is poorly understood. The structural analysis of complex I revealed that the M64 forms a nonpolar interaction Y59 in the ND6, Y59 in the ND6 interacts with E34 of ND4L, and L60 of ND6 interacts with the Y114 of ND1. These suggested that the m.14484T > C mutation may perturb the structure and function of complex I. Mutant cybrids constructed by transferring mitochondria from lymphoblastoid cell lines of one Chinese LHON family into mtDNA-less (ρo) cells revealed decreases in the levels of ND6, ND1 and ND4L. The m.14484T > C mutation may affect mitochondrial mRNA homeostasis, supported by reduced levels of SLIRP and SUPV3L1 involved in mRNA degradation and increasing expression of ND6, ND1 and ND4L genes. These alterations yielded decreased activity of complex I, respiratory deficiency, diminished mitochondrial ATP production and reduced membrane potential, and increased production of reactive oxygen species in the mutant cybrids. Furthermore, the m.14484T > C mutation promoted apoptosis, evidenced by elevating Annexin V-positive cells, release of cytochrome c into cytosol, levels in apoptotic proteins BAX, caspases 3, 7, 9 and decreasing levels in anti-apoptotic protein Bcl-xL in the mutant cybrids. Moreover, the cybrids bearing the m.14484T > C mutation exhibited the reduced levels of autophagy protein LC3, increased levels of substrate P62 and impaired PINK1/Parkin-dependent mitophagy. Our findings highlighted the critical role of m.14484T > C mutation in the pathogenesis of LHON.